High-Power Laser Therapy Improves Healing of the Equine Suspensory Branch in a Standardized Lesion Model - Pluim, Mathilde; Martens, Ann; Vanderperren, Katrien; van Weeren, René; Oosterlinck, Maarten; Dewulf, Jeroen; Kichouh, Mimoun; Van Thielen, Bert; Koene, Marc H. W.; Luciani, Antonio; Plancke, Lukas; Delesalle, Cathérine (Frontiers in Veterinary Science, 2020)
Abstract High-power laser therapy is often used as a treatment for human sport injuries but controlled standardized studies on its efficacy are lacking. The technique has also been introduced in the equine field and recently promising results were reported in a retrospective study focusing on 150 sporthorses suffering from tendinopathy and desmopathy of the SDFT, DDFT, suspensory ligament and suspensory branches. The goal of the present study was to evaluate the effect of high-power laser in a standardized lesion model in horses. Lesions were created in all lateral suspensory branches of 12 warmblood horses. In each horse, 2 of the 4 lesioned branches were treated daily with a multi-frequency high-power laser for 4 weeks. Color Doppler ultrasonography were performed during and after the treatment period. Six horses were euthanized 4 weeks post-surgery (short-term) and 6 were further rehabilitated until 6 months and then euthanized (long-term). High-field MRI evaluation was performed on all cadaver limbs. On ultrasound, transverse size of the lesion was significantly smaller after 2- and 3 months (p=0.026 and p=0.015) in the treated branches. The expected post-surgery enlargement of the lesion circumference and cross-sectional area (CSA) over time, was significantly lower in the short-term laser treated group (p=0.016 and p=0.010). Treated lesions showed a significantly increased Doppler signal during treatment (p<0.001) compared with control. On MRI, in the short and long-term group, the CSA of the lesions was significantly smaller (p=0.002), and the mean signal significantly lower in the treatment groups (p=0.006). This standardized controlled study shows that multi-frequency high-power laser therapy significantly improves healing of a suspensory branch ligament lesion.